Determination of Exposure Factors and Interlock System Base On Fuzzy Logic In X-Ray Conventional Generator - Sugeng Santoso; Muhammad Haddin; Eka Nuryanto Budi Susila (Universitas Islam Sultan Agung, 2018)
One of the utilization of x-Ray on medical area is radiogram. Result of the radiogram can determine patient diagnosis of disease. More clearly the result of imaging, can bring pecise and accurate diagnosis. To solve that problem, we need to calculate distance between X-Ray tube and object, type of film, screen kaset, and also situation or condition of body weight either mature, child or infant to determine exposure factors. Exposure factors is kilovolt, miliampere and time. That exposure factors means electrical load toward X-Ray tube to produce radiant intensity. Interlock system is used to prevent useless generation of X-Ray and doesn’t produce diagnostic value. In this research using fuzzy logic to determine exposure factors on thorax examination which is implemented in software by using pre-defined reference data. By input distance, body weight, body height in software will be obtained appropriate exposure factors setting for radiografer. By determining the focus distance of the appropriate (valid) film, then the fuzzy logic system can build an interlock system that will prevent the useless x-rays. The results showed that data taken from a radiographer in a local hospital in Semarang compared with the output of exposure factor software was appropriate and when interlock system is activated the fuzzy control system can prevent the generation of x-rays